2021
DOI: 10.1177/16094069211016106
|View full text |Cite
|
Sign up to set email alerts
|

Resilient Research in the Field: Insights and Lessons From Adapting Qualitative Research Projects During the COVID-19 Pandemic

Abstract: The onset of the COVID-19 pandemic has seen the implementation of unprecedented social distancing measures, restricting social interaction and with it the possibility for conducting face-to-face qualitative research. This paper provides lessons from a series of qualitative research projects that were adapted during the COVID-19 pandemic to ensure their continuation and completion. By reflecting on our experiences and discussing the opportunities and challenges presented by crises to the use of a number of qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 48 publications
3
100
0
Order By: Relevance
“…[33] (p. 1061). Alternative methods were quickly proposed and adopted by academics, especially those employing qualitative methodologies, including conducting digital ethnographies, shifting to phone and online surveys, interviewing, and creating focus groups using digital platforms such as Zoom, WhatsApp, and others [34][35][36][37][38][39][40]. Several scholars have proposed research agendas to collate revisions in research topics, data collection methods, and modes of dissemination stemming from pandemic restrictions and ruptures in the status quo of data collection [41][42][43].…”
Section: Methodsmentioning
confidence: 99%
“…[33] (p. 1061). Alternative methods were quickly proposed and adopted by academics, especially those employing qualitative methodologies, including conducting digital ethnographies, shifting to phone and online surveys, interviewing, and creating focus groups using digital platforms such as Zoom, WhatsApp, and others [34][35][36][37][38][39][40]. Several scholars have proposed research agendas to collate revisions in research topics, data collection methods, and modes of dissemination stemming from pandemic restrictions and ruptures in the status quo of data collection [41][42][43].…”
Section: Methodsmentioning
confidence: 99%
“…While, overall, our project had relative success in recruiting participants remotely during the COVID-19 pandemic, we note that remote data collection that relies on digital technologies is not always appropriate in every context and situation [79][80][81]. Researchers should consider how the pandemic may have affected the participants' well-being and their ability to participate in research [81].…”
Section: Plos Onementioning
confidence: 94%
“…While, overall, our project had relative success in recruiting participants remotely during the COVID-19 pandemic, we note that remote data collection that relies on digital technologies is not always appropriate in every context and situation [79][80][81]. Researchers should consider how the pandemic may have affected the participants' well-being and their ability to participate in research [81]. In addition, while our participants did not voice concerns about technological barriers, multiple studies have demonstrated inequities in access to and ability to use mobile devices (e.g., smartphones, tablets, or laptops) for research participation along with challenges related to poor connectivity.…”
Section: Plos Onementioning
confidence: 96%
See 1 more Smart Citation
“…Prior to the COVID-19 pandemic, online focus groups (FGs) and individual interviews (IDIs) were being used with increasing frequency across multiple disciplines (Braun et al 2017;Salmons 2016), a trend that the pandemic has accelerated and mainstreamed, at least for the near-term (Saarijärvi and Bratt 2021;Rahman et al 2021). A key advantage of online data collection has always been that a researcher can collect data remotely and from individuals across multiple locations (Comley and Beaumont 2011).…”
Section: Introductionmentioning
confidence: 99%